Interconnecting the violences of men: continuities and intersections in research, policy and activism - Seymour, Kate; Pease, Bob; Strid, Sofia; Hearn, Jeff (Routledge advances in feminist studies and intersectionality, 2025)
This book aims to expand and enrich understandings of violences by focusing on gendered continuities, interconnections and intersections across multiple forms and manifestations of mens violence